2021
DOI: 10.1001/jamaophthalmol.2021.1708
|View full text |Cite
|
Sign up to set email alerts
|

Association of Allergic Conjunctivitis With Health-Related Quality of Life in Children and Their Parents

Abstract: IMPORTANCE Allergic conjunctivitis (AC) is one of the most common allergic diseases and is especially problematic in children and adolescents. The course of AC is generally prolonged and often recurs. Understanding the health-related quality of life (QOL) of both children with AC and their parents would be useful.OBJECTIVE To evaluate the association between AC and health-related QOL in children and their parents. DESIGN, SETTING, AND PARTICIPANTSA prospective case-control study was conducted at Zhongshan Opht… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 40 publications
(69 reference statements)
1
23
0
2
Order By: Relevance
“…Another study reported that children with allergic conjunctivitis experienced reduced quality of life. 62 Additionally, 1 recent study using commercial insurance claims data including 12 005 189 participants found that children younger than 18 years with strabismus have higher odds of mental illnesses, including anxiety and depression, than children without strabismus. However, 64.5% and 46.0% in the strabismus and control group, respectively, also harbored at least 1 systemic comorbid condition, such as cancer of the brain and nervous system or leukemia, which was adjusted for in the multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Another study reported that children with allergic conjunctivitis experienced reduced quality of life. 62 Additionally, 1 recent study using commercial insurance claims data including 12 005 189 participants found that children younger than 18 years with strabismus have higher odds of mental illnesses, including anxiety and depression, than children without strabismus. However, 64.5% and 46.0% in the strabismus and control group, respectively, also harbored at least 1 systemic comorbid condition, such as cancer of the brain and nervous system or leukemia, which was adjusted for in the multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Data on allergic rhinitis, asthma, food allergy, eczema, and atopic dermatitis 7 -all diseases that often coexist-report similar findings as noted in this study. 1 Better understanding the outcomes associated with AC in adolescents compared with young children and adults and development of pediatric AC QOL questionnaires that can be compared with other eye disease QOL questionnaires are just a few interesting areas of possible future investigation that may improve health care outcomes of patients with AC.…”
Section: Related Article Page 830mentioning
confidence: 99%
“…There were significantly more boys in the AC group than in the control group (83.7% vs 42.7%). 1 Boys are more commonly affected by vernal keratoconjunctivitis, so it is not surprising that more boys than girls were represented in the disease group. However, not controlling for this discrepancy in the control group potentially introduces a confounding effect.…”
mentioning
confidence: 99%
“…The major symptoms of AC are itching, swelling, and tearing, and in some severe cases, photophobia and pain could develop due to the involvement of the cornea [ 5 , 6 ]. Patients suffering from AC have a lower health-related quality of life and impaired socioeconomic status [ 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%